2004
DOI: 10.1177/1077559504269192
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis of the Relationship Between Reported Child Maltreatment and Special Education Eligibility Among Poor Children

Abstract: This study presents data from the first large-scale longitudinal study to track the involvement of children reported for maltreatment in both the special education and child welfare systems. A range of state and local administrative databases were combined and cross-sector service histories were established for 7,940 children who had received Aid to Families With Dependent Children between 1993 and 1994. The authors address the following questions: (a) Is maltreatment associated with entry into special educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(99 citation statements)
references
References 24 publications
6
89
1
3
Order By: Relevance
“…This is consistent with the Harm/ Evidence model of substantiation that asserts that substantiation is not equivalent to verifying the presence of maltreatment but rather a label used when sufficient evidence and/ or risk of harm exists to permit family court intervention if needed (Drake, 1996). Further, several studies have found that many unsubstantiated cases include harm or risk of harm to the child English et al, 2002Jonson-Reid, Drake, Kim, Porterfield & Han, 2004;Leiter, Myers, & Zingraff, 1994).…”
Section: Characteristics Of Index Reportsupporting
confidence: 53%
“…This is consistent with the Harm/ Evidence model of substantiation that asserts that substantiation is not equivalent to verifying the presence of maltreatment but rather a label used when sufficient evidence and/ or risk of harm exists to permit family court intervention if needed (Drake, 1996). Further, several studies have found that many unsubstantiated cases include harm or risk of harm to the child English et al, 2002Jonson-Reid, Drake, Kim, Porterfield & Han, 2004;Leiter, Myers, & Zingraff, 1994).…”
Section: Characteristics Of Index Reportsupporting
confidence: 53%
“…Despite substantial research documenting the relative equivalent risk for unsubstantiated or substantiated reports of child maltreatment [18][19][20][21][22], a records purge cycle was enacted by law in 2003, which mandated the purging of any unsubstantiated case without recurrence or service within 3 years and any substantiated cases without recurrence or services within 10 years. In other words, either the subsequent receipt of formal service or a recurrence before the purge date extends the retention period for the record.…”
Section: Official-report Maltreatment/foster Datamentioning
confidence: 99%
“…While there are several forms of child maltreatment, the general theme observed is that severe maltreatment negatively impacts physiological and emotional well-being and may result in trauma-related disorders (Perry & Pollard, 1998). The impact of the associated physiological and emotional strain may extend to the point where normative education skills development and school performance are impaired (Jonson-Reid, Drake, Kim, Porterfield, & Han, 2004). A wide array of other disorders, including those related to prenatal and perinatal exposure to toxins that impede infant development, those directly caused by birth complications, and learning and education deficit factors associated with low socioeconomic status (SES), affect both school readiness and subsequent designations of special education needs.…”
Section: Special Education Needsmentioning
confidence: 99%